2011
DOI: 10.3390/cancers3011158
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Heat Shock Factors in Tumorigenesis: Therapeutical Potential

Abstract: Heat Shock Factors (HSF) form a family of transcription factors (four in mammals) which were named according to the discovery of their activation by a heat shock. HSFs trigger the expression of genes encoding Heat Shock Proteins (HSPs) that function as molecular chaperones, contributing to establish a cytoprotective state to various proteotoxic stresses and in pathological conditions. Increasing evidence indicates that this ancient transcriptional protective program acts genome-widely and performs unexpected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 129 publications
(171 reference statements)
1
24
0
Order By: Relevance
“…Cancer cells often further their survival and growth in hostile environments by increasing the expression of key SRFs such as CIRP, HSF1, HIF1, and NRF2 (45)(46)(47)(48). One of the consequences of SRF expression in hypoxic cancer cells is increased mutagenesis (29), similar to the SIM of TNRs observed here.…”
Section: Discussionsupporting
confidence: 54%
“…Cancer cells often further their survival and growth in hostile environments by increasing the expression of key SRFs such as CIRP, HSF1, HIF1, and NRF2 (45)(46)(47)(48). One of the consequences of SRF expression in hypoxic cancer cells is increased mutagenesis (29), similar to the SIM of TNRs observed here.…”
Section: Discussionsupporting
confidence: 54%
“…HSF1 inhibition, shown to be effective in reducing cell survival of several cancer cell types [15], has not been yet investigated in PEL cells. To evaluate the effect mediated by its reduction, we knocked down this molecule by specific siRNA and observed that it led to reduction of PEL cell survival (Fig.…”
Section: Knock-down Of Hsf1 By Specific Sirnas Reduces Pel Cell Survimentioning
confidence: 99%
“…In particular, phospho-STAT3 interacts with HSF1 promoting its transcriptional activity [13]. Besides inducing the expression of HSPs, HSF1 positively regulates other prosurvival pathways in cancer cells, that is the reason why it is itself emerging as a promising target in anticancer therapy [14,15]. However, its constitutive expression and its role in PEL cell survival have not been investigated yet.…”
Section: Introductionmentioning
confidence: 96%
“…[8] which has the ability to induce cell death through destabilizing the mitotic spindle and by disrupting topoisomerase II function, thereby leading to DNA fragmentation [9][10][11][12]. Because cancer cells have an increased mitotic rate, they are consequently susceptible to the action of celastrol [13,14]. As well as its apoptosis-inducing effects, celastrol has at lower concentrations the ability to activate the heat shock response that leads to cytoprotection of the cell [15].…”
Section: Introductionmentioning
confidence: 98%